Infrastructure and Economic Growth in East Asia - Straub, Stéphane (World Bank, Washington, DC, 2012)
This paper examines whether infrastructure investment has contributed to East Asia's economic growth using both a growth accounting framework and cross-country regressions. For most of the variables used, both the growth accounting exercise and cross-country regressions fail to find a significant link between infrastructure, productivity and growth. These conclusions contrast strongly with previous studies finding positive and significant effect for all infrastructure variables in the context of a production function study. This leads us to conclude that results from studies using macro-level data should be considered with extreme caution. The Authors suggest that infrastructure investment may have had the primary function of relieving constraints and bottlenecks as they arose, as opposed to directly encouraging growth.